The Impact of Motivation, Educational Background, and Financial Incentives on Students' Career Aspirations in the Sharia Banking Sector - Rita Alfin (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2023)
The purpose of this research was to ascertain the impact of motivation, educational attainment, and financial incentives on students majoring in Islamic Banking at the Faculty of Islamic Economics and Business, State Islamic University Satu Tulungagung's desire in pursuing a career in the Islamic banking sector. The sort of associative research used in this study is approached quantitatively. The Faculty of Islamic Economics and Business's student body of 87 respondents from the study sample of students majoring in Islamic Banking was utilized to gather the research's data. The validity and reliability test, normality test, traditional assumption test, multiple linear regression test, t-test (partial), F test (simultaneous), and coefficient of determination test (R2) are the data analysis techniques employed. The study's findings indicate that (1) motivation has a favorable and considerable impact on career interest in the Islamic banking sector, both partly and concurrently. (2) A person's educational background has a favorable and substantial impact on their desire in a job in the Islamic banking sector. (3) Financial benefits considerably and favorably influence career interest in the Islamic banking sector. (4) Interest in a job in the Islamic banking sector is favorably and considerably influenced by motivation, educational background, and financial appreciation.